Superior outcomes (but at higher costs) of non‐operative management with interval appendectomy over immediate surgery in appendicitis with abscess: Results from a large adult population cohort. Issue 2 (2nd July 2019) - Watanabe, Ryohei; Otsuji, Ayako; Nakamura, Yoichi; Higuchi, Tadashi; Takahashi, Asako; Saito, Tomoaki; Enomoto, Toshiyuki; Quero, Giuseppe; Diana, Michele; Dallemagne, Bernard; Marescaux, Jacques; Saida, Yoshihisa; et al.
Abstract: Introduction: The aim of this study was to compare surgical outcomes and hospitalization costs between immediate surgery and non‐operative management followed by interval appendectomy in adults presenting with appendicitis with abscess. Methods: From 2003 to 2015, 3316 patients presented with appendicitis, including 101 who presented with appendicular abscess. Between 2003 and 2006, 33 patients with appendicular abscess were managed with emergency operations (emergency group). Non‐operative management followed by interval appendectomy was implemented in 2007 and offered to 68 patients during the study period. Of these patients, 64 patients underwent the procedure (interval group), and 4 patients refused. Results: Non‐operative management was successful in 76.6% of cases (49/64 patients) in the interval group. Operative time and length of hospital stay were similar between the emergency and interval groups. In the interval group, blood loss, the need for extended resection, and overall postoperative morbidity were significantly lower than in the emergency group ( P  < 0.01, respectively). Medical costs for surgery in the interval group were lower than in the emergency group ($4512 vs $6888, P = 0.002), but this group's total medical costs were higher ($9591 vs $6888, P  < 0.01). Conclusion: The interval strategy is associated with a reduced need for extended resection, lower postoperative morbidity, and a shorter length of hospital stay. However, total medical costs for the interval strategy are higher than those for emergency operations in cases of appendicular abscess in adults.